Chronic Obstructive Pulmonary Disease: official diagnosis and treatment guidelines of the Czech Pneumological and Phthisiological Society; a novel phenotypic approach to COPD with patient-oriented care - Koblizek, Vladimir; Chlumsky, Jan; Zindr, Vladimir; Neumannova, Katerina; Zatloukal, Jakub; Zak, Jaroslav; Sedlak, Vratislav; Kocianova, Jana; Zatloukal, Jaromir; Hejduk, Karel; Pracharova, Sarka; Czech Pneumological and Phthisiological Society (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
BACKGROUND: COPD is a global concern. Currently, several sets of guidelines, statements and strategies to managing COPD exist around the world. METHODS: The Czech Pneumological and Phthisiological Society (CPPS) has commissioned an Expert group to draft recommended guidelines for the management of stable COPD. Subsequent revisions were further discussed at the National Consensus Conference (NCC). Reviewers' comments contributed to the establishment of the document's final version. DIAGNOSIS: The hallmark of the novel approach to COPD is the integrated evaluation of the patient's lung functions, symptoms, exacerbations and identifications of clinical phenotype(s). The CPPS defines 6 clinically relevant phenotypes: frequent exacerbator, COPD-asthma overlap, COPD-bronchiectasis overlap, emphysematic phenotype, bronchitic phenotype and pulmonary cachexia phenotype. TREATMENT: Treatment recommendations can be divided into four steps. 1(st) step = Risk exposure elimination: reduction of smoking and environmental tobacco smoke (ETS), decrease of home and occupational exposure risks. 2(nd) step = Standard treatment: inhaled bronchodilators, regular physical activity, pulmonary rehabilitation, education, inhalation training, comorbidity treatment, vaccination. 3(rd) step = Phenotype-specific therapy: PDE4i, ICS+LABA, LVRS, BVR, AAT augmentation, physiotherapy, mucolytic, ABT. 4(th) step = Care for respiratory insufficiency and terminal COPD: LTOT, lung transplantation, high intensity-NIV and palliative care. CONCLUSION: Optimal treatment of COPD patients requires an individualised, multidisciplinary approach to the patient's symptoms, clinical phenotypes, needs and wishes. The new Czech COPD guideline reflects and covers these requirements.
Keywords: chronická obstrukční plicní nemoc; Pulmonary Medicine; Patient Care Planning; Pulmonary Disease, Chronic Obstructive; konsensus; pneumologie; Societies, Medical; Consensus; plánování péče o pacienty; Humans; Česká republika; lidé; Patient-Centered Care; společnosti lékařské; péče orientovaná na pacienta; Czech Republic